دور التنمية المستدامة لمنظمات الأعمال في حماية حقوق المستهلك : من وجهة نظر تسويقية - لحول، سامية; باشا، ريمة; بولطيف، سعيدة Boulatif, Saidah (جامعة عين شمس - كلية التربية - الجمعية المصرية للقراءة والمعرفة, 2018)
من خلال الطرح السابق، يهدف هذا البحث إلى تحديد دور التنمية المستدامة لمنظمات الأعمال في حماية حقوق المستهلك، من وجهة نظر تسويقية. ويتم ذلك من خلال إبراز أساسيات التنمية المستدامة لمنظمات الأعمال والتعرف على العلاقة ما بين هذا المفهوم والمفهوم التسويقي. كما سيتم التعرف على حقوق المستهلك، باعتباره إنسان، وكيف يمكن للمسؤولية الاجتماعية لمنظمات الأعمال حماية حقوق المستهلك من خلال التسويق المستدام. وأظهرت النتائج المستخلصة من البحث مساهمة التنمية المستدامة لمنظمات الأعمال في حماية حقوق المستهلك من خلال الالتزامات التي تتحملها أثناء قيامها بمختلف الممارسات والتي تطبقها على المستهلك عن طريق التسويق المستدام، والمتمثل في التسويق الأخضر (المنتوج الأخضر، السعر الأخضر، الترويج الأخضر، والتوزيع الأخضر)، التسويق المسؤول (الجودة، الابتكار، أخلقة الادارة، الاتصال المسؤول) والتسويق المجتمعي (الدور التربوي أو التعليمي، حساسية المواطنة للمستهلكين، وتضع نفسها في سجل الالتزام).
Increasing awareness of the need for the participation of business organizations in all development processes as a full partner in the daily life of society. The society started to take on new and more complex dimensions, Business organizations must respond to the expectations and aspirations of the community. Rather, they must participate in philanthropy, voluntary campaigns, Health and environment, taking into account human rights, especially the rights of consumers and workers, and try to develop new behaviors in society and commitment to fair competition and away from monopoly and satisfy consumers. Through the previous thesis, this research aims to identify the role of sustainable development of business organizations in protecting consumer rights, from a marketing point of view. This is done by highlighting the basics of sustainable development for business organizations and identifying the relationship between this concept and marketing concept. Consumer rights, as a human being, will also be recognized and how corporate social responsibility can protect consumer rights through sustainable marketing. The results of the study showed the contribution of sustainable development to business organizations in protecting consumer rights through the commitments they undertake in carrying out various practices that they apply to consumers through sustainable marketing, namely green marketing (green product, green price, green promotion and green distribution) (Quality; innovation, management structure; responsible communication) and community marketing (educational or educational role; citizen sensitivity to consumers, and setting themselves up in the commitment register).
Keywords: التنمية المستدامة -- منظمات الأعمال -- حماية المستهلك -- التسويق الأخضر